EVALUASI PELAKSANAAN RINTISAN SEKOLAH DASAR BERTARAF INTERNASIONAL - Yulianto, Eva (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, 2014)
Abstract: this research aims to know successful achievement program in the international school that includes (1) a contextual component , (2) input component which includes student qualification, the teacher qualification, curriculum implementation and the state of the infrastructure, (3) the components process ari learning process, and (4) the components product that is the competence of graduates. This study used a deskriptif quantitative approach which is also supported by qualitative data. The analysis results concluded that the RSDBI program implementation in Jakarta seen from (1) the contextual component covered, financing with achievement of 73%, management / school management 70% (2), component evaluation include 40% learners (SKL) an evaluation component, 42% teacher component evaluation, the evaluation component of the curriculum 56%, the evaluation component of infrastructure 49%, (3) process evaluation components 49% (learning) and 42% (assessment), and (4) evaluation of component product is at 53% achievementKeywords: RSBI, program evaluation, elementary schoolAbstrak:Penelitian ini bertujuan untuk mengetahui ketercapaian keberhasilan penyelenggaraan program Rintisan Sekolah Bertaraf Internasional yang meliputi (1) komponen konteks, (2) komponen input yang meliputi kualifikasi peserta didik, kualifikasi tenaga pendidik, pelaksanaan kurikulum serta keadaan sarana dan prasarana, (3) komponen proses yaitu proses pembelajaran, dan (4) komponen produk yaitu kompetensi lulusan. Penelitian ini menggunakan pendekatan deskriptif kuantitatif yang juga didukung oleh data kualitatif. Hasil analisis penelitian menyimpulkan bahwa penyelenggaraan Program RSDBI di DKI Jakarta dilihat dari (1) komponen konteks meliputi pembiayaan dengan capaian 73%, pengelolaan/manajemen sekolah 70% (2), evaluasi komponen input meliputi evaluasi komponen peserta didik (SKL) 40%, evaluasi komponen pendidik 42%, evaluasi komponen kurikulum 56%, evaluasi komponen sarana dan prasarana 49%, (3) evaluasi komponen proses 49% (pembelajaran) dan 42% (penilaian), dan (4) evaluasi komponen pro-duk berada pada capaian 53%.Kata kunci: RSBI, Evaluasi Program, Sekolah Dasar